Critical Study on the Tube-to-Chip Luer Slip Connectors - Etxeberria, Leire; Aguilera, Unai; Garcia de Madinabeitia, Pablo; Saez, Alberto; Zaldua, Ane M.; Vilas-Vilela, José L.; Fernández, Luis; Llobera, Andreu (Frontiers in Medical Technology, 2022)
Luer slip is one of the gold standards for chip-to-world interface in microfluidics. They have outstanding mechanical and operational robustness in a broad range of applications using water and solvent-based liquids. Still, their main drawbacks are related to their size: they have relatively large dead volumes and require a significant footprint to assure a leak-free performance. Such aspects make their integration in systems with high microchannel density challenging. To date, there has been no geometrical optimization of the Luer slips to provide a solution to the mentioned drawbacks. This work aims to provide the rules toward downscaling the Luer slips. To this effect, seven variations of the Luer slip male connectors and five variations of Luer slip female connectors have been designed and manufactured focusing on the reduction of the size of connectors and minimization of the dead volumes. In all cases, female connectors have been developed to pair with the corresponding male connector. Characterization has been performed with a tailor-made test bench in which the closure force between male and female connectors has been varied between 7.9 and 55 N. For each applied closure force, the test bench allows liquid pressures to be tested between 0.5 and 2.0 bar. Finally, the analysis of a useful life determines the number of cycles that the connectors can withstand before leakage.